Challenges of ecological momentary assessments to study family leisure: Participants' perspectives. (1st January 2022) - Chandler, Kelly D.; Hodge, Camilla J.; McElvaine, Kara; Olschewski, Ericka J.; Melton, Karen K.; Deboeck, Pascal
Abstract: Scholars have documented the research tradeoffs of using ecological momentary assessments (EMA) to study daily life. Less is known about participants' perspectives. The aim of this research note was to delineate the challenges of participating in a 14-day EMA study of family leisure described by 41 individuals (mothers, fathers, and adolescents) from 14 families to inform future family leisure studies using EMA. Participants identified three potential challenges: repetitive questions, inconvenient signals, and short response windows. Despite these challenges, the majority of participants indicated that they would recommend a similar study to others. The reality that so many families feel squeezed for time requires scholars to be aware of participants' perspectives and make accommodations accordingly. Otherwise, advances in family leisure research and programs will be thwarted. Ecologically valid, yet time-intensive, research methods like EMA could provide rich data about how to promote fulfilling family leisure experiences and well-being.